Analisis Letak Geografis Sekolah Terhadap Quality Of Learning Di SMK TV Watampone Kabupaten Bone - Maharani, Anisa; Aziz, Muh Bachtiar (Adaara: Jurnal Manajemen Pendidikan Islam, 2024)
Â This study discusses "Analysis of School Geographical Location on Learning Quality at SMK TV Watampone, Awangpone District, Bone Regency". The author uses qualitative research methods through field research whose data collection uses observation, interview, and documentation techniques. This study aims to describe the geographical location of SMK TV Watampone School on the quality of learning. The results showed that the geographical location of the school did not have a significant influence on the quality of learning at SMK TV Watampone Kecamatan Awangpone Bone Regency.